Micro-structural phenomena in agate/chalcedony: spiral growth. (3rd October 2018) - Götze, Jens; Berek, Harry; Schäfer, Klaus
Abstract: Agates with spectacular micro-structural features were found in volcanic rocks at several occurrences in the Saar-Nahe region (Germany). These agates include spirals of several tens up to several hundreds of μm in size within zones lacking the characteristic structural agate banding. A combined mineralogical study by polarising microscopy, scanning electron microscopy, cathodoluminescence microscopy and spectroscopy, and electron backscatter diffraction provided evidence that the spirals consist of well-ordered trigonal α-quartz, whereas the surrounding matrix is composed of strongly disordered or amorphous SiO2 phases. The quartz micro-crystals show a systematic rotation of the crystal orientation perpendicular to the direction of the spiral loops indicating helical growth. It is assumed that the spiral growth is initiated by dislocations with a screw component. The lacking symmetry of the strongly disordered or amorphous matrix initiated a curved development by a screw dislocation in a system far from equilibrium. The atoms/molecules are packed into spiral layers, which is energetically favoured in comparison with the incorporation into plane crystal faces. Such self-organisation growth and polymerisation initiated by a screw dislocation can produce variable spiral morphologies sometimes resembling living forms.